Motivation in ESL: A Literature Review - Naghmeh Babaee (Canadian Society for Studies in Education, 2012)
Motivation in second language acquisition (SLA) refers to the attempt and desire to learn a language and positive attitudes toward learning it (Dornyei, 1994). Motivation in SLA has been extensively investigated in different contexts (Feng & Chen, 2009; Wu & Wu, 2008; Melendy, 2008; Wang, 2007; Lamb, 2007). Still, more research seems necessary to shed light on this area because of the potential impact of motivation on SLA. This literature review compares and contrasts the research questions, settings, theoretical frameworks, and results of several studies on motivation. Following this, implications for English as a Second Language (ESL) teachers, learners, parents, and textbook designers are provided. Finally, the limitations of these studies are highlighted and suggestions for further research are discussed.